Digitised Body and Self Among Generation Z on Instagram in West Sumatra - Rahmaini, Indah Sari; Zuldesni, Zuldesni; Irwansyah, Ade; Syukri, Khariful (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
This study aims to determine how the Digitized body/self is perceived by Gen Z on Instagram and explore the challenges faced by Generation Z in constructing and producing digital identities in their daily activities. This study uses a digital sociology perspective and Deborah Lupton's concept of the digitized body in the context of the West Sumatra community. This study uses a qualitative approach using netnographic research types such as observation of visual content, captions, profile descriptions, and interaction patterns that complement the explanation of their digital practices. This research is complemented by in-depth interviews with Instagram users from Generation Z based on predetermined criteria. The results show that Generation Z forms the digitalization of the body and self through the practice of audience segmentation based on goals, namely using multiple accounts, using anonymous accounts, selecting posts based on audience groups per account, and differentiating the digital self they want to show based on the account's purpose. This form of digitalization reflects the difference between online representation and their real-world self.